Analisis Penyelesaian Perkara Persaingan Usaha Tidak Sehat pada Pelaku Usaha Sejenis Ditinjau dari Undang-Undang No. 5 Tahun 1999 - Raska, Ery Charmelita (UM Purwokerto Press, 2024)
Settlement of unfair business competition cases against similar business actors using Law Number 5 Year 1999. The settlement of unfair business competition disputes can be conducted through litigation (through the court) or non-litigation (outside the court). The purpose of this study is to analyze the settlement of unfair business competition cases in similar business actors and the impact caused as a whole. The research method used is normative juridical. The results of the research describe the elements of business competition violations, case settlement through arbitration, the impact caused, and legal protection efforts for consumers. The settlement of cases through non-litigation channels through arbitration by business actors who want to resolve disputes is considered more effective than through litigation. The impact of unfair business competition on consumers can cause unreasonable prices, reduce consumer choice, and hinder the development of science and technology.